Effects of reactor pressure and inlet temperature on n-butane/dimethyl ether oxidation and the formation pathways of the aromatic species - Bekat, Tugce; Inal, Fikret (WILEY, 2016)
Oxidation of n-butane/dimethyl ether (DME)/O-2/Ar system was studied by chemical kinetic modeling in a tubular reactor operated adiabatically and at constant pressure. Effects of the reactor pressure on the formation of various major, minor, and trace oxidation products were investigated for two different pressures (1 and 5 atm) and at six different inlet temperature values (700, 800, 900, 1100, 1300, and 1500 K). The analysis was carried out for two different concentrations of dimethyl ether in the inlet fuel mixture (20 and 50 mol %). Higher pressure (5 atm) resulted in higher mole fractions of methane, vinylacetylene, and cyclopentadiene; and lower mole fractions of formaldehyde, acetylene, acetaldehyde, ethane, propargyl, and propane. The mole fractions of CO and CO2 were not affected considerably by the pressure change. The main formation routes of benzene were developed at two different inlet temperature values (1100 and 1300 K), and the main precursors participating in these routes were found to be propargyl, propene, and diacetylene. A skeletal mechanism was developed for the oxidation of n-butane/DME mixture from the detailed mechanism by reduction of the elementary reactions by 79%, and it was tested for accuracy by comparison with the data from the literature. (c) 2015 American Institute of Chemical Engineers Environ Prog, 35: 230-240, 2016
Keywords: dimethyl ether; n-butane; kinetic modeling; aromatics; skeletal mechanism; EMISSION CHARACTERISTICS; THERMAL-DECOMPOSITION; SHOCK-TUBE; HYDROCARBON; PYROLYSIS; BUTANE; DME; MECHANISM; ALLENE; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology